PENGARUH LINGKUNGAN KELUARGA, PENGETAHUAN KEWIRAUSAHAAN, DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Henny Rachmawati; Waspodo Tjipto Subroto (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractInterest Entrepreneurship person grow because factors from the family environment, entrepreneurial knowledge person, and entrepreneurial motivation. purpose of this research was to analyze the effect from the family environment, entrepreneurial knowledge, and entrepereneurial motivation on interest entrepereneurship of students economic education study program. This research used quantitative approach with correlational type. The population was students of the economic education study program 2018 and 2019 totalling 122 students, and the research sample using simple random sampling technique in determining 93 sample was obtained. Data collection used questionnaire and techniques data analysis used multiple linier regression analysis. The results of this study showed: (1) family environment partially has not effect interest entrepereneurship of students (2) Entrepreneurial knowledge partially has an effect interest entrepereneurship of students (3) motivation of entrepreneurial partially has an effect interest entrepereneurship of students (4) family environment, entrepreneurial knowledge, and motivation of entrepreneurial simultaneously has a significant effect interest entrepereneurship of students.Keywords: family environment, entrepreneurial knowledge, motivation of entrepreneurial, interest of entrepreneurship.